Softdrink Habit, Breakfast and Physical Activity Associated with Overweight in SMA Negeri 7 Bengkulu - Putri, Frita Aulia Eka; Maigoda, Tonny Cortis; Rizal, Ahmad; Jumiyati, Jumiyati; Kusdalinah, Kusdalinah; Hari Hariadi (Open Global Scientific Journal, 2024)
Overweight and obesity can occur in individuals of all age groups, including adolescents, who are experiencing a phase of rapid growth. This study aims to determine the relationship between soft drink consumption, breakfast habits, and physical activity with the incidence of excess body weight among adolescents at SMA Negeri 7 Bengkulu City in 2024. The research is an analytic observational study employing a cross-sectional design. A total of 54 class XI students were selected through simple random sampling. Data on soft drink consumption and breakfast habits were collected using the FFQ form, while physical activity data was gathered using the GPAQ questionnaire. The incidence of excess body weight was determined by measuring height and weight with a microtoise and a weight scale. Univariate and bivariate data analyses were conducted using the chi-square test with a significance level of α = 0.05. The results indicated that the majority of respondents frequently consume soft drinks (75.9%), rarely eat breakfast (80.7%), and engage in sufficient physical activity (71.8%). There is a significant relationship between the habit of consuming soft drinks and the incidence of excess weight in adolescents (p = 0.007), between breakfast habits and the incidence of excess weight (p < 0.001), and between physical activity and the incidence of excess weight (p = 0.002).